The Dynamics of Contemporary Islamic Thought in the “Muhammadiyah Is Not Wahhabi” Narrative: A Framing Analysis Based on Robert N. Entman’s Framework - Ari Dwi Aditya; Ida Suryani Wijaya; A. Rivai Beta (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze the construction of the “Muhammadiyah Is Not Wahhabi” narrative and to examine how such a discourse reflects broader dynamics of contemporary Islamic thought in Indonesia. This research employs a qualitative approach using library research methods and applies Robert N. Entman’s framing analysis model, which consists of four analytical dimensions: defining problems, diagnosing causes, making moral judgments, and recommending treatments. The data were collected from digital religious discourses, scholarly literature, and relevant media texts discussing Muhammadiyah, Wahhabism, and Islamic identity. The findings indicate that the narrative frames Muhammadiyah as an autonomous Islamic reform movement with distinctive historical, theological, and methodological foundations that differ from Wahhabism. The discourse also portrays Wahhabism as an external ideological influence while positioning Ahmad Dahlan’s intellectual legacy as a source of legitimacy for Muhammadiyah’s independent identity. Furthermore, the study reveals that digital religious narratives function not only as instruments of da‘wah but also as arenas for ideological contestation, identity construction, and the reinterpretation of Islamic thought in the digital age. The novelty of this research lies in its integration of framing analysis with contemporary Islamic thought studies, demonstrating how digital discourse actively shapes theological boundaries and religious identities within Indonesian Islam.